The Effect of Smart Box Media Based on Local Wisdom on The Cognitive Abilities of Young Children - Leni Sriningsih; Gunawan Gunawan; Efan Yudha Winata (Indonesian Journal of Elementary and Childhood Education, 2026)
This study aims to determine the effect of local wisdom-based smart box media on the cognitive abilities of early childhood. The research method employed a quantitative experimental approach with a One-Group Pretest-Posttest Design. The research population included all 18 children in Group B at TK Merdeka, with sampling conducted using the total sampling technique. Data collection techniques were carried out through observation using checklist assessment sheets and documentation. The main findings indicate a significant positive effect after the treatment, where the average score increased from 68.84 (beginning to develop category) during the pretest to 84.5 (developing as expected category) during the posttest. The results of the hypothesis testing using the paired sample t-test reinforce these findings, yielding a significance value of 0.000 < 0.05. Consequently, this study proves that the use of local wisdom-based smart box media effectively improves children's cognitive abilities in the aspects of remembering and understanding. The implication is that the utilization of manipulative educational game tools (APE) that integrate local cultural elements can serve as a solution-oriented alternative for physical learning media to optimize children's cognitive potential without relying on digital devices.